2018
DOI: 10.3389/fphar.2018.00446
|View full text |Cite
|
Sign up to set email alerts
|

Matrine Directly Activates Extracellular Heat Shock Protein 90, Resulting in Axonal Growth and Functional Recovery in Spinal Cord Injured-Mice

Abstract: After spinal cord injury (SCI), reconstruction of neuronal tracts is very difficult because an inhibitory scar is formed at the lesion site, in which several axonal growth inhibitors, such as chondroitin sulfate proteoglycans (CSPG), accumulate. We previously found that matrine, a major alkaloid in Sophora flavescens, enhanced axonal growth in neurons seeded on CSPG coating. The aims of this study were to investigate therapeutic effects of matrine in SCI mice and to clarify the underlying mechanism. Matrine wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…As a result, resistance against proteolysis is changed. Using this method, many ligand and receptor pairs have been identified ( Qu et al, 2016 ; Yang et al, 2017 ; Tanabe et al, 2018 ). In the current study, cell lysate of astrocytes was incubated with recombinant NLK or vehicle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, resistance against proteolysis is changed. Using this method, many ligand and receptor pairs have been identified ( Qu et al, 2016 ; Yang et al, 2017 ; Tanabe et al, 2018 ). In the current study, cell lysate of astrocytes was incubated with recombinant NLK or vehicle.…”
Section: Resultsmentioning
confidence: 99%
“…It has not been clarified whether NLK decreases CSPGs levels at the lesion site. We previously reported that several agents showed axonal growth activity without the alteration at the lesion site ( Teshigawara et al, 2013 ; Tanabe et al, 2018 ). From our in vitro experiment (Figure 2D ), NLK promoted axonal growth in the presence of CSPG.…”
Section: Discussionmentioning
confidence: 99%
“…Though not a large number of differential m6A genes are identified, many of which are related to neural injury and repair. For instance, HSP90 participates in axonal regeneration and functional recovery after SCI (Takata et al., 2003; Tanabe et al., 2018). Lama2 released from the CNS resident pericytes can enhance oligodendrocyte progenitor cell differentiation and thus promote CNS remyelination (De La Fuente et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Through drug affinity response target stability (DARTS) system screening, Matrine can directly bind heat shock protein 90 (HSP90), through neutralization. Specific blockade of anti-HSP90 by antibody can inhibit the growth of axons induced by matrine, suggesting that the improvement of SCI by matrine depends on the regulation of HSP90 (Tanabe et al, 2018). Matrine can also upregulate the expression of protein lipid protein, increase the number of…”
Section: Spinal Cord Injury/encephalomyelitismentioning
confidence: 99%